Minimum wages policy towards the employers in SME industry - Muhammad Zulfaris Mohd Salleh; Azwan Abdullah (Faculty of Entrepreneurship and Business,UMK, 2015)
The minimum wages policy in Malaysia was announced by the Prime Minister in his Budget Speech on 15 October 2010 and it is expected to be implemented in all stages by the year 2013.There are three purposes of this case study: (1) To identify factors influencing employers on the implementation of minimum wages policy.(2) To find the impacts towards the implementation of minimum wages policy to the employers.(3) To explore the readiness among employers regarding the implementation of minimum wages policy gazette by government. A qualitative method was used in this study and the data was collected by using the purposive sampling. The study participants consists of the SMEs entrepreneurs that make business in Kota Bharu area. The results of this study reveals that the implementation of minimum wages policy give the positive impacts to the employees and at the same time most of the employers still not complied this policy because of financial problems. Therefore, this study concludes that diversified incentives should be undertaken by government with special focus on provide adequate trainings and educations, provide subsidies to the entrepreneurs, reduce the SMEs burden by giving exemption of tax and exclude the GST implementation on them. In addition, the government should review and re-organize the existing policy in order to increase the number of employers that implement this policy in their business and firms and at the same time increase the employees’ satisfaction and happiness.